If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -3(x + -7) = 57 Reorder the terms: 15x + -3(-7 + x) = 57 15x + (-7 * -3 + x * -3) = 57 15x + (21 + -3x) = 57 Reorder the terms: 21 + 15x + -3x = 57 Combine like terms: 15x + -3x = 12x 21 + 12x = 57 Solving 21 + 12x = 57 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 12x = 57 + -21 Combine like terms: 21 + -21 = 0 0 + 12x = 57 + -21 12x = 57 + -21 Combine like terms: 57 + -21 = 36 12x = 36 Divide each side by '12'. x = 3 Simplifying x = 3
| (x^2+7)/(3x^2-5) | | -8(p+6)=-104 | | -6(x-6)=84 | | -7b+9y=2(x-1) | | -6(x-6)=74 | | 4x(27x+6)=35 | | 6(8n+5)=222 | | 5(2x+7)=105 | | 1/2y+3=-17 | | 3/5=4/x | | 6x^2=1.5 | | 6(4+8x)+4x=-184 | | 4/5(x-15)=8 | | (x^2+7)*(3x^2-5)=0 | | 3x+7-6x=1 | | -4-8(1-6x)=-396 | | c+1/-3=-21 | | 4/7=x/5 | | 2x+26=5x+6 | | 11=3x | | -4-8(1-6x)=-386 | | 8+15z-3=6z+109-4z | | 5k+1=2k+2 | | 9x=8x+9 | | -5x+3/4=-1/3 | | -6k-4k=10 | | 4/7.00000014=x/5 | | 12-10-k=-36 | | 6(2x-1)-7(2x+3)=2(x-1)+2(x-3) | | 3x^2+12x=-9 | | 2+2k=8 | | 3/5=4.2/x |